Quantity Does Not Always Mean Quality: The Importance of Qualitative Social Science in Conservation Research. Issue 10 (3rd October 2017) - Rust, Niki A.; Abrams, Amber; Challender, Daniel W. S.; Chapron, Guillaume; Ghoddousi, Arash; Glikman, Jenny A.; Gowan, Catherine H.; Hughes, Courtney; Rastogi, Archi; Said, Alicia; Sutton, Alexandra; Taylor, Nik; et al.
ABSTRACT: Qualitative methods are important to gain a deep understanding of complex problems and poorly researched areas. They can be particularly useful to help explain underlying conservation problems. However, the significance in choosing and justifying appropriate methodological frameworks in conservation studies should be given more attention to ensure data are collected and analysed appropriately. We explain when, why, and how qualitative methods should be used and explain sampling strategies in qualitative studies. To improve familiarity with qualitative methods among natural scientists, we recommend expanding training in social sciences and increasing collaboration with social scientists. Given the scale of human impacts on the environment, this type of nuanced analytical skill is critical for progressing biodiversity conservation efforts.